Study of modification of photo active material with carbon nanostructures for polymer solar cell applications. (September 2017) - Sahare, Sanjay; Ghoderao, Prachi; Dey, Abhijeet; Datar, Suwarna; Bhave, Tejashree
Graphical abstract: Highlights: The study demonstrated the role of carbon nano structure additives (MWCNT and GNR) in P3HT:PCBM through PA C-AFM. These nano structures have improved absorption of light, built-in potential and charge transfer pathways in photoactive layer PA C-AFM demonstrate one order of magnitude change in localised current for MWCNT and GNR added P3HT:PCBM blend. GNR additive based solar cell shows ∼62% enhancement in the photon to current conversion efficiency compared to P3HT:PCBM solar cell. Abstract: Assorted techniques are always adapted to improve the efficiency in hybrid solar cells. One such technique is to use a combination of lower & higher band gap materials, and modified morphology of polymer: fullerene blends. The aim of all these efforts is to achieve efficient charge separation and improvement in current. In this work, the photoactive layer was modified by using two additives; (i) Multiwalled Carbon Nanotubes (MWCNT) and (ii) Graphene Nanoribbon (GNR). Basic understanding of such modifications cannot be understood till the fabrication and testing of the device. To explore the effects of such modifications on the device properties, we have studied the modified photoactive layer before the device fabrication and observed the change in optoelectronic properties under light exposure. These samples were analysed with UV–vis spectroscopy, high resolution transmission electron microscopy and photon assisted conducting atomic force microscopy (PA C-AFM). The localised current in the photoactive films with GNR additive was found significantly higher. Further, the photovoltaic device was fabricated in ambient conditions. Power conversion efficiency of the photoactive material was improved by 62% using GNR as additive, while MWCNT as additives has showed improvement by 31% in fabricated solar cell under open atmospheric conditions.